Causes of mortality in South American fur seal pups (Arctophoca australis gracilis) at Guafo Island, southern Chile (2004–2008). Issue 1 (29th November 2011) - Seguel, Mauricio; Pavés, Héctor; Paredes, Enrique; Schlatter, Roberto
Abstract As part of population dynamics studies of the South American fur seal (Arctophoca australis gracilis) rookery at Punta Weather in Guafo Island (43°36'S, 74°43'W), the causes and extent of pup mortality were monitored. During four breeding seasons, daily counts of live and dead pups were carried out to determine pup production and pup mortality. Dead pups were retrieved from the rookery to perform necropsies. The mean pup production was 1, 735.5 ± 336 pups and the mean pup mortality up to 12 wk old was 6.0%± 2.6%. The major causes of death were enteritis with microscopic lesions of bacteremia (28.4%), starvation (23.5%), drowning (21%), trauma (19.8%), and stillbirths (2.5%). Enteritis with microscopic lesions of bacteremia, and starvation had higher incidence during January (beginning and middle of the breeding season) while most trauma and drowning occurred during February (end of the breeding season). In the 2006–2007 breeding season there was an increase in mortality due to starvation and trauma. Most pup deaths at Guafo Island are generated by extrinsic factors; therefore, additional studies that assess the impact of environmental changes and fishing activities, are needed in order to determine the exact causes of the decline of this species along Chilean coasts.